1992
DOI: 10.1002/cne.903150404
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional consequences of neonatal deafferentation in the superficial layers of the hamster's superior colliculus

Abstract: Intracellular recording and horseradish peroxidase (HRP) injection techniques were used to evaluate the effects of neonatal enucleation upon the structural and functional properties of cells in the superficial retinorecipient laminae of the hamster's superior colliculus (SC). The physiological recordings confirmed previous results that normally visual superficial layer neurons develop somatosensory receptive fields in the enucleated animals. This study further showed that all of the physiological subclasses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…7). The dendritic shape of roughly half of the reconstructed neurons could be classified into one of the previously described classes of dendritic morphologies in the upper layers of the SC (Langer and Lund 1974;May 2006;Mooney et al 1992), whereas the remaining neurons had no clearly recognizable structure (Table 3). This is the first direct evidence, to our knowledge, that a diverse population of neuron types in the SGS receives functional retinal input as early as P3.…”
Section: Resultsmentioning
confidence: 99%
“…7). The dendritic shape of roughly half of the reconstructed neurons could be classified into one of the previously described classes of dendritic morphologies in the upper layers of the SC (Langer and Lund 1974;May 2006;Mooney et al 1992), whereas the remaining neurons had no clearly recognizable structure (Table 3). This is the first direct evidence, to our knowledge, that a diverse population of neuron types in the SGS receives functional retinal input as early as P3.…”
Section: Resultsmentioning
confidence: 99%
“…It is highly likely that the strong projection from the nBIC to the dSC that we observed at least in part underlies the auditory sensitivity of rat SC neurons (Gaese and Johnen 2000). The contribution of sSC inputs to the visual responses of rat dSC neurons is not known, although studies in other rodents have shown that those responses are derived from the sSC (Mooney et al 1992). Our results therefore suggest that, at around the time of eye opening and the onset of hearing (Friauf 1992), there exists a welldeveloped circuitry that could support multisensory interactions.…”
Section: Cross-modal Connectivity In the Superior Colliculusmentioning
confidence: 85%
“…The basic idea behind this, then, is that every portion of a dendrite will have a limited temporal window in which activity-dependent processes can effect its structure. Although there are instances in which dendrites that have already undergone development can be altered (e.g., Mooney et al 1992), the signal that initiates this large-scale modification is itself a large-scale event, such as deafferentation, that requires a change at that scale.…”
Section: Dendrites As Learning Structuresmentioning
confidence: 99%